Transformasi Digital Wakaf di Indonesia - Lubis, Syafrina Yuni; Wati, Patma; Samri, Yenni (Al-Sharf: Jurnal Ekonomi Islam, 2024)
In the current digital era, waqf management, especially cash waqf, has taken digital form, for example in the form of waqf financial technology. Cash waqf is a waqf made by a person, group of people, organization or legal entity in the form of cash. This research aims to examine the digital transformation of waqf in Indonesia. This type of research is library research by searching and collecting references relevant to the study topic. The findings from this research are that there are several waqf platforms and websites that are easy to access, including berkah waqf or berkahwakaf.id, so berkah or jasaberkah.id/wakaf, salaam or esalaam.co.id/wakaf and wallet dhuafa or pacudhuafa.org/ waqf. Cash Waqf offers many interesting opportunities, not only for developing infrastructure but also providing growth opportunities for other parties, in particular: for education, health, sanitation and social services.